Peranan Polisi Lalu Lintas Dalam Meningkatkan Kesadaran Hukum Penggunaan Helm Bagi Pengemudi Sepeda Motor Roda Dua (Studi Kasus: Polresta Pulau Ambon dan Pulau-Pulau Lease) - Rince Monita Sari Molle; Julianus Edwin Latupeirissa; Anna Maria Salamor (PATTIMURA Law Study Review, 2023)
This research discusses the role of the traffic police in increasing legal awareness of the use of helmets for two-wheeled motorbike drivers. Purposes of the research: to analyze and understand the application of sanctions against drivers who violate them, as well as explain the efforts made by the police to increase legal awareness. Methods of the Research: This research uses empirical juridical research methods with legal material processing techniques and then data examination is carried out in the form of data classification. Results of the Research: The results of the research show that the level of legal awareness of the use of helmets among the people of Ambon City is still very minimal or low, so it requires cooperation between law enforcement officials and the community so that the level of awareness increases and a conducive atmosphere is created.